“Então vamos aprender a brigar, tio?”: os jogos de oposição como possibilidade pedagógica no ensino das lutas na escola. - Neves, Kelvin Jhonn dos Santos (Universidade Federal do Tocantins, 2021)
The present work aimed to understand the point of view of children from the 4th year of elementary school in a public full-time school in the city of Porto Franco - MA, about the struggles, from their cultural productions and pedagogical interventions with definition games. The class listed for the study was composed of 27 children, 15 boys and 12 girls, aged between 9 and 10 years. That said, we carried out a field research, of an interventional nature, divided into two stages: in the first, a round of conversation took place and the application of thematic drawings with the children, as a way to map introductory understandings these subjects have in relation to the struggles; the second, corresponded to a block of 6 (six) techniques with the content fights, through games of choice, held between the months of September and October of the year 2019, at the school. A qualitative analysis of field records in common perceives that children's initial understanding of struggles, to a large extent, was made up of an association with violent behaviors, apprehended in daily life, inside and outside the school, with strong media appeal. It is concluded, from the interventions, that the distortion in the representation of the fights and the association with the violence theme, previously presented by the children, was re-signified with the games accordingly.